Dynamics of Kinship Addressing among Millennial Teenagers on Social Media - Melati, Inka Krisma; Hasanah, Uswatun; Iswatiningsih, Daroe (Universitas Dian Nuswantoro, 2023)
The use of language in kinship addressing has changed following the times. This change includes forming new terms often found on social media such as YouTube, Instagram, and Facebook. This research aims to (1) describe the forms of kinship addressing among millennial teenagers on social media, (2) explain the meaning of kinship addressing among millennial teenagers on social media, and (3) explain the context of the dynamics of kinship greetings among millennial teenagers on social media. This research uses a qualitative descriptive method with a pragmatic approach. The data source for this research is the kinship addressing expressed by millennial teenagers on social media sites such as YouTube, Instagram, and Facebook. This research data contains kinship addressing and the dynamics of the development of kinship addressing. The collection technique uses note-taking techniques and screen capture techniques. The data analysis technique is a matching method for selecting determining elements (PUP). The results of the research concluded that (1) 2 forms of kinship addressing were found among millennial teenagers in the mass media, namely kinship addressing with shortening patterns and forms of kinship addressing based on religion, (2) 26 kinship addressing of millennial teenagers on social media were found which experienced dynamics, and ( 3) background, social and age contexts are found